Analysis of Store Location and Atmosphere the Effect on Consumer Purchase Interest at Centro Department Store - Toni Yoyo; Nana Sutisna; Berlin Silaban (eCo-Fin, 2019)
This study aims to determine the analysis of the location and atmosphere of the store and its influence on consumer buying interest at the Centro Department Store. The sample in this study amounted to 100 respondents are all consumers who shop at the Centro Department Store. Data was collected through questionnaires, and data processing in this study used SPSS version 23.0. The sampling technique used is probability sampling with random sampling method. The research model used is a descriptive research model which describes systematically and accurately about the factors studied. The results of data processing obtained a multiple linear equation Y = 10.104 + 0.426 X1 + 0.363 X2, meaning that for every 1 point increase or decrease in location, consumer buying interest at the Centro Department Store will increase or decrease by 0.426 and each increase or decrease If the store atmosphere decreases by 1 point, then consumer buying interest at the Centro Department Store will increase or decrease by 0.363. In addition to calculating the relationship between the independent variable and the dependent variable, this study also calculated the relationship between variables. The correlation between location and consumer buying interest is 0.426, the correlation between store atmosphere and consumer buying interest is 0.363, it can be said that the relationship between the three variables is quite strong and positive. From the results of the F test, model 1 obtained a value of 249.862 and model 2 obtained a value of 143.897, where the value is greater than the F table of 3.09, then H0 is rejected and Ha is accepted. From the results of the t test, it was found that the location count was 3.456, and the store atmosphere t was 3.377, where the value was greater than the t table 1.66055, then H0 was rejected and Ha was accepted, meaning that there was a significant relationship between the location and the shop atmosphere on consumer buying interest